THE EXISTENCE OF BALINESE MASK DANCE DRAMA IN THE MILLENNIAL GENERATION IN GIANYAR REGENCY - I Gede Tilem Pastika; I Wayan Sugita; Cokorda Krisna Dwiyoga (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2026)
This qualitative research aims to examine the phenomenon and analyze the forms of existence of the Balinese Mask Dance Drama among the millennial generation in Gianyar Regency. Traditionally, this art demands multi-competency and a pawintenan ritual, usually performed by mature dancers. However, contemporary observation shows that millennials are actively involved, significantly influencing the evolution of art due to their distinct lifestyle. Data were collected through observation, interviews, and documentation. The analytical framework used is the aesthetics of existentialism. The results demonstrate that millennial mask artists ensure the art's existence through specific innovations. These include: integrating dance movements that imitate viral trends (such as TikTok dances) while maintaining core Balinese movements; mask shape innovations (e.g., movable mouth parts); emphasizing costume colors; and using multiple languages (Indonesian, English, slang) to address current social dynamics. Furthermore, digital media is leveraged for accompaniment music and promotion, serving as a primary learning source.